Vanpo sustainability: the impact of requirements for economic sustainability on visual arts non-profit organisations in Johannesburg - French, James E (My University, 2016)
The Civil Society sector in South Africa has been experiencing a funding crisis for the past 20 years. The arts represent a small portion of Civil Society, and the visual arts a small part of the art. This research considers how these visual arts non-profit organisations (VANPOs) in this economic microsphere have been challenged to survive and sustain their missions in what is a competitive, fluctuating and complex environment. This study scrutinizes the concept of sustainability and the visual arts non-profit sector’s capacity for implementation of economically sustainable projects in the current economic and funding environment in South Africa. It outlines the complex and challenging nature of sustainability for VANPOs. The VANPOs, all small organisations, have limited human and cash resources to implement sustainability strategies while fulfilling their missions. Furthermore the funding environment focuses on short-term project grants and production-oriented efforts. This does not offer the organisations much opportunity towards long-term organisational development nor strategic resourcefulness. At the same time they struggle to remain compliant with government regulations and donor requirements. This research considers methods of assessing sustainability and the perspectives of professionals involved in the management of VANPOs. It examines the challenges they have faced in finding ways to implement sustainability and in the implementation of ‘sustainable’ projects. The brief case studies focus on how five VANPOs have responded to diminishing funding.
A research report submitted to the University of the Witwatersrand Faculty of Humanities, School of Arts, in fulfilment of the requirements of a Masters degree in Arts and Culture Management Johannesburg 2015
Keywords: Arts--Economic aspects--South Africa; Nonprofit organizations--South Africa; Sustainability--Economic aspects